ПРОФЕСІЙНИЙ РОЗВИТОК ПЕДАГОГІЧНИХ ПРАЦІВНИКІВ ЗАКЛАДІВ ФАХОВОЇ ПЕРЕДВИЩОЇ ОСВІТИ (Innovative professional education, 2022)
The article deals with the issue of professional development ofteaching staff of institutions of vocational pre-higher education; selection andcombination of various forms, methods, technologies; self-development and self-education
Keywords: pedagogical workers, methods, forms, self-education, pedagogical technologies